Effect of Gibberellic Acid (GA3) Inflorescence Application on Content of Bioactive Compounds and Antioxidant Potential of Grape (Vitis L.) ‘Einset Seedless’ Berries - Kapłan, M.; Najda, A.; Klimek, K.; Borowy, A. (South African Journal of Enology and Viticulture, 2018)
Gibberellic acid (GA3) is a plant growth regulator widely used in the cultivation of seedless grape varieties to increase their yield. Hormonisation treatment has beneficial effects on yield size and quality, yet its influence on the level of biologically active compounds and grape antioxidant activity has not yet been studied extensively yet. Clusters of 11-year-old ‘Einset Seedless’ grapevines trained according to the single Guyot pruning style were sprayed with GA3 at 100, 200 or 300 mg/L dose once, twice or three times. Fruit harvested on 25 September were immediately examined for acidity, extract content, biologically active substances and antioxidant capacity using the DPPH test. In addition, correlations occurring between some parameters measured were calculated. Hormonisation had a negative effect on the content of extract, flavonoids and ascorbic acid, while it had no effect on the anthocyanin level. The antioxidant activity determined by the DPPH assay depended on dose and the number of treatments, and the analysed parameters were shown to decrease significantly with increasing application number. Gibberellic acid at 100 and 300 mg/L application rates had a significantly increased DPPH level compared to the control and 200 mg/L dose. The single GA3 treatment, and when applied three times, and application rates at 100 and 200 mg/L were shown to have a significant influence on phenolic acid content. The level of tannins after a single GA3 treatment and a 300 mg/L dose increased significantly.